Optimal control of electromechanical aerospace actuators for reduction of energy losses - Kalra, Shrey (2019)
With continuous efforts to optimize performance and reduce operational and maintenance costs, the aircraft industry is rapidly pushing towards the concept of all or more-electric aircraft (MEA). Today’s flight control systems being largely hydraulically powered, are gradually turning into electromechanical actuators (EMAs) within the MEA framework. However, integration and exploitation of EMAs is highly dependent on their thermal behavior. Owing to their high power-density, aerospace EMAs are highly susceptible to overheating which limits their sizing and capability. Among other ways to mitigate this problem, control system design too plays a major role in altering the system’s thermal behavior, especially during transient operation. The aim of this study is to develop an alternative control strategy and explore the possibility of heat reduction in the actuator by careful selection and tuning of controller gains. With the final goal of limiting actuator temperatures, a design-ratio selection technique is developed using bandwidths of current-to-speed and speed-to- position feedback loops respectively. This technique is then adopted in order to examine the heat variation trends by model simulation. Furthermore, the controller design allows the client flexibility to demand specific requirements such as design bandwidth, while also minimizing heat generation. Simulation results show that substantial heat savings, up to 18%, are possible by this method when operating in some flight regimes. Simultaneously, the possibility of setting a minimum dynamic stiffness is also explored, especially to account for cases where heat savings are not found to be as feasible. This method, parallel to other ongoing studies, contributes to alleviate the overheating problem in EMAs and allows the industry to incline further towards more-electric, and ultimately, all-electric technologies in the future.